A mixed‐methods study of cultural beliefs about dementia and genetic testing among Mexicans and Mexican‐Americans at‐risk for autosomal dominant Alzheimer's disease. Issue 5 (17th June 2019) - Withers, Mellissa; Sayegh, Philip; Rodriguez‐Agudelo, Yaneth; Ernstrom, Karin; Raman, Rema; Montoya, Lucy; Zuno‐Reyes, Angelica; Mosieri, Chizoba; Matute, Esmeralda; Ringman, John M.
Abstract: Trials to prevent autosomal dominantly inherited Alzheimer's disease (ADAD) are critical and timely. However, cultural beliefs about AD and genetic testing may preclude informed consent and participation, especially among racial/ethnic minorities. This mixed‐methods study examines cultural beliefs about AD and genetic screening among at‐risk populations of Mexican heritage. We surveyed 86 Mexican and 37 Mexican‐American family members of patients with ADAD and interviewed 18 respondents in Mexico to explore perceptions and knowledge regarding AD and genetic testing. While most respondents understood that AD is inherited in their families, they also had limited understanding of the genetic mechanisms behind AD. Many believed that AD is a normal part of aging or that it is a mental illness caused by bad habits. However, beliefs that AD is caused by a curse or God's will were uncommon. The interviews demonstrated that very few at‐risk respondents understood their own risk for harboring the mutation causing AD in their family. Once informed, most expressed a strong interest in genetic testing, largely motivated by the desire to be better prepared for the development of AD. Health professionals treating and investigators enrolling members from families with ADAD cannot assume that they fully understand the nature of the illness; therefore, providers should provide comprehensive information about ADAD and genetic testing.